Feasibility of Dialysate Bolus-Based Absolute Blood Volume Estimation in Maintenance Hemodialysis Patients - Krenn, Simon; Schmiedecker, Michael; Schneditz, Daniel; Hödlmoser, Sebastian; Mayer, Christopher C.; Wassertheurer, Siegfried; Omic, Haris; Schernhammer, Eva; Wabel, Peter; Hecking, Manfred (Frontiers in Medicine, 2022)
Background Absolute blood volume (ABV) is a critical component of fluid status, which may inform target weight prescriptions and hemodynamic vulnerability of dialysis patients. Here, we utilized the changes in relative blood volume (RBV), monitored by ultrasound (BVM) upon intradialytic 240mL dialysate fluid bolus-infusion one hour after hemodialysis start, to calculate the session-specific ABV. With the main goal of assessing clinical feasibility, our sub-aims were to (i) standardize the BVM-data read-out; (ii) determine optimal time-points for ABV-calculation, “before-” and “after-bolus”; (iii) assess ABV-variation. Methods We used high-level programming language and basic descriptive statistics in a retrospective study of routinely measured BVM-data from 274 hemodialysis sessions in 98 patients. Results Regarding (i) and (ii), we automatized the processing of RBV-data, and determined an algorithm to select the adequate RBV-data points for ABV-calculations. Regarding (iii), we found in 144 BVM-curves from 75 patients, that the average ABV ± standard deviation was 5.2±1.5L and that among those 51 patients who still had ≥2 valid estimates, the average intra-patient standard deviation in ABV was 0.8L. Twenty-seven of these patients had an average intra-patient standard deviation in ABV <0.5L. Conclusions We demonstrate feasibility of ABV-calculation by an automated algorithm after dialysate bolus-administration, based on the BVM-curve. Based on our results from this simple “abridged” calculation approach with routine clinical measurements, we encourage the use of multi-compartment modelling and comparison with reference methods of ABV-determination. Hopes are high that clinicians will be able to use ABV to inform target weight prescription, improving hemodynamic stability.